2020
DOI: 10.1186/s13014-020-01619-y
|View full text |Cite
|
Sign up to set email alerts
|

ATM mutations improve radio-sensitivity in wild-type isocitrate dehydrogenase-associated high-grade glioma: retrospective analysis using next-generation sequencing data

Abstract: Background: To identify the association between somatic ataxia-telangiectasia mutated (ATM) mutations and improved radio-sensitivity, we retrospectively reviewed next-generation sequencing data from patients diagnosed with isocitrate dehydrogenase (IDH)-wildtype high-grade glioma. Methods: We included 39 individuals with (IDH)-wildtype high-grade glioma (diffuse astrocytoma n = 2, anaplastic astrocytoma n = 10, and glioblastoma n = 27) not subjected to gross tumor resection and undergoing radiation therapy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…ATM orchestrates the cellular DDR to cytotoxic DNA DSBs induced by radiation (141,142). Overexpression of ATM indicates radiation resistance in breast cancer cells (143), whereas deficiency of ATM showed radiation sensitizer effects in multiple cancer types (144)(145)(146)(147). Interestingly, more studies have focused on the radiation sensitizer effects that are dependent on the cell cycle and proliferation status (148,149).…”
Section: Atm-chk2mentioning
confidence: 99%
“…ATM orchestrates the cellular DDR to cytotoxic DNA DSBs induced by radiation (141,142). Overexpression of ATM indicates radiation resistance in breast cancer cells (143), whereas deficiency of ATM showed radiation sensitizer effects in multiple cancer types (144)(145)(146)(147). Interestingly, more studies have focused on the radiation sensitizer effects that are dependent on the cell cycle and proliferation status (148,149).…”
Section: Atm-chk2mentioning
confidence: 99%
“…Our data also showed that gene expression of the HR pathway was inversely associated with RT response. The inhibition of HR components has enhanced radiosensitivity in glioblastoma cells [ 27 , 28 ], hence cells with a higher expression of HR genes may be more likely to survive than tumours which have a lower baseline expression [ 4 , 6 , 17 , 29 ]. Further investigation is needed to explore these results in more depth.…”
Section: Discussionmentioning
confidence: 99%
“…In our work, Ki-67 had no significant association with the prognosis, probably because most patients had high Ki-67 values. Although the experience is limited, other works have reported more adverse metabolic conditions (higher SUV and MTV) in IDH-wt and high Ki-67 tumors [ 14 , 40 ].…”
Section: Discussionmentioning
confidence: 99%